2020
DOI: 10.1177/0009922820903043
|View full text |Cite
|
Sign up to set email alerts
|

Parental Knowledge and Attitudes About Universal Lipid Screening Among Children Aged 9 to 11 Years

Abstract: Nationally recommended universal lipid screening (ULS) in children aged 9 to 11 years is low. Little is known about parents’ understanding of screening. We conducted a survey exploring parental knowledge and attitudes regarding ULS. Of 91 parent respondents, 81.3% were female, 69.2% were non-Hispanic white, 90.1% had a college/graduate degree, and 63.7% had a family history of abnormal cholesterol. Overall, 45.5% agreed that ULS should be done for all children, 30.8% disagreed, and 23.1% were unsure. Parents’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Conversely, a regional study in the United States on parental support for ULS did not nd an association between parental support and their knowledge about family history of abnormal cholesterol or CVD. The same study did identify a lack of understanding about the utility of ULS in children as a potential barrier to parents supporting ULS (Kern L et al 2020). We hypothesize that an increased public awareness and education regarding FH as a condition and the bene ts of ULS in children may in uence parental attitudes toward screening in the United States.…”
Section: Parents Support Universal Lipid Screeningmentioning
confidence: 84%
“…Conversely, a regional study in the United States on parental support for ULS did not nd an association between parental support and their knowledge about family history of abnormal cholesterol or CVD. The same study did identify a lack of understanding about the utility of ULS in children as a potential barrier to parents supporting ULS (Kern L et al 2020). We hypothesize that an increased public awareness and education regarding FH as a condition and the bene ts of ULS in children may in uence parental attitudes toward screening in the United States.…”
Section: Parents Support Universal Lipid Screeningmentioning
confidence: 84%
“…A recent survey found that parental support for ULS is significantly associated with their attitudes about universal screening rather than their knowledge about cholesterol, family history of CVD, or demographics. 21 Future research could further examine parental attitudes about ULS, pediatrician communication about ULS with patients/families, the barriers to and motivators for completing lipid screening, and the effectiveness of in-clinic phlebotomy and/or point-of-care testing for increasing screening rates.…”
Section: Discussionmentioning
confidence: 99%